Diseño de un sistema de producción y almacenamiento de energía eléctrica, a través de la transformación de energía motriz humana en un equipo de gimnasio. (2022)
In this project, the design of an energy generating system was carried out based on the work generated in the exercise bikes in the gym of the Tenerife residential complex in Bogotá, with the purpose of finding an efficient way of generating energy capable of reducing energy consumption from from the public electricity network, as well as reduce energy costs per month. For this, a form of clean energy generation is proposed, reducing the environmental pollution produced by power plants that produce said energy through the burning of fossil fuels, releasing carbon dioxide and other harmful gases that pollute the environment.